Policing labor trafficking in the United States - Farrell, Amy (Trends in organized crime, 2020)
Despite new mandates to identify and respond to labor trafficking crimes, US law enforcement struggles to integrate labor trafficking enforcement with traditional policing routines and roles. As a result, human trafficking enforcement has primarily focused on sex trafficking and few labor trafficking cases have been identified and prosecuted. This study utilizes data from 86 qualitative interviews with municipal, state, county and federal law enforcement, victim service providers and labor trafficking victims in four US communities to inform our understanding of police responses to labor trafficking in local communities. Through the coding of these interviews across a series of themes, we identify three major challenges that impact police identification and response to labor trafficking crimes. These include lack of clarity about the definition of labor trafficking, lack of institutional readiness to address labor trafficking, and routines of police work that undermine police responsiveness to labor trafficking in local communities. Considering these challenges, we explore strategies law enforcement can take to improve identification, including developing non-traditional partnerships with labor inspection and local regulatory agencies. Additionally, interview data suggest a role for the police in ensuring labor trafficking victims are safe and their needs are met, regardless of the outcomes of the criminal justice process. This is the first study to examine police responses to labor trafficking from the perspective of police, service providers and victims.